Analisis Metakomunikasi Politik dalam Proyek Pemindahan Ibu Kota Negara (IKN) Nusantara - Sukma, Agus Hitopa; Soepriyadi, Irzan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
The relocation of the State Capital (IKN) from Jakarta to Nusantara is one of the largest strategic projects initiated by the government. This policy is based on the excessive burden on Jakarta and the economic disparity between Java Island and other regions in Indonesia. The remarkably swift legislative process for the IKN Law has created a public perception that speed was prioritized over thorough deliberation, which has the potential to erode public trust. This study aims to reveal the political metacommunication behind the IKN relocation project. The analysis was conducted to uncover the hidden meanings, power dynamics, and underlying intentions behind political statements and actions related to IKN. This research uses a political metacommunications analysis approach, which serves to uncover the